A 110-year history of the Swiss Neurological Society (SNG) through the biosketches of its first 42 presidents. Issue 2 (1st August 2018) - Bassetti, Claudio L; Hess, Christian W; Steck, Andreas; Ludin, Hans-Peter
The Swiss Neurological Society (SNG) was founded in 1908. In the 1930s, a pre- and postgraduate neurological curriculum and the recognition of neurology as medical specialty followed. In the 1950–1960s, first independent university departments were created in the country. On the occasion of the 110th anniversary of the SNG, the biosketches of its first 42 presidents (including C. von Monakow, R. Bing, M. Minkowski, H. Krayenbühl and M. Mumenthaler) are presented. The multidisciplinary and international influences that contributed to the development of neurology in Switzerland are discussed in the context of the national and international scientific, medical and political history.